2020
DOI: 10.1103/physrevc.102.024908
|View full text |Cite
|
Sign up to set email alerts
|

Critical point fluctuations: Finite size and global charge conservation effects

Abstract: We investigate simultaneous effects of finite system size and global charge conservation on thermal fluctuations in the vicinity of a critical point. For that we consider a finite interacting system, which exchanges particles with a finite reservoir (thermostat), comprising a statistical ensemble that is distinct from the common canonical and grand canonical ensembles. As a particular example the van der Waals model is used. The global charge conservation effects strongly influence the cumulants of particle nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Event-by-event fluctuations, especially the high-order cumulants, are strongly affected by global conservation laws [35][36][37], requiring large corrections to the grand-canonical distributions. Other mechanisms include volume fluctuations [38][39][40], finite system size [41], as well as non-equilibrium dynamics such as memory effects [42] or hadronic phase evolution [43]. Proper modeling of these effects is thus required for analyzing the experimental data quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Event-by-event fluctuations, especially the high-order cumulants, are strongly affected by global conservation laws [35][36][37], requiring large corrections to the grand-canonical distributions. Other mechanisms include volume fluctuations [38][39][40], finite system size [41], as well as non-equilibrium dynamics such as memory effects [42] or hadronic phase evolution [43]. Proper modeling of these effects is thus required for analyzing the experimental data quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…ative values up to sixth order at large rapidity acceptance at √ s NN = 3 GeV. Those strong rapidity acceptance dependence are mainly attributed to the effects of baryon number conservations [64][65][66][67]. In addition, we observed that if we randomly drop 7% protons in each event then the cumulants are close to the deuteron formation case.…”
Section: Let Us First Discuss the Validity Of Centrality Bin Width Co...mentioning
confidence: 54%
“…In order to quantitatively describe the experimental observed cumulants of net proton multiplicities, more sophisticated and realistic dynamical modeling are required from the theoretical side [56,57]. Besides, a number of effects play their role, including the subject of the proper equation of state [58][59][60], of the unknown parameters of the Ising-to-QCD mapping [61], of the critical transport coefficients [62][63][64][65], of the finite size, finite size scaling and global charge conservation in the vicinity of a CP [66][67][68][69][70], of the non-critical baseline for the cumulants of net-proton number fluctuations [71], and of the nonuniform temperature/chemical potential effects [72]. In addition, further connections between the criticality and the experimental observables have been established through theoretical efforts [73][74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%